How big data development influences enterprise green technology innovation? The moderating role of digital inclusive finance - Cheng, Kaiming; Liu, Shucheng (Technological and Economic Development of Economy, 2025)
Existing research thoroughly discussed the dividend effect of big data development (BDD), but few analyses have been conducted from a micro perspective of enterprises’ green development. With the exogenous policy shock of the National Big Data Comprehensive Pilot Zone, this study takes Chinese A-share listed companies as the research objects. We adopt the difference-in-differences model to systematically assess the impact of BDD on enterprise green technology innovation (GTI) and the moderating role played by digital inclusive finance (DIF) between the two. The study reveals that BDD significantly contributes to enterprise GTI. Furthermore, the facilitating effect of BDD on GTI is more significant in large enterprises, state-owned enterprises, enterprises with higher degrees of local government data openness, and enterprises with higher levels of the real economy. The moderating effect test shows that DIF significantly moderates BDD and enterprise GTI. Mechanism tests show that BDD promotes enterprise GTI through three channels: strengthening regional environmental regulation, alleviating enterprise financing constraints, and enhancing enterprise human capital. This paper provides valuable ideas for emerging economies planning to promote sustainable growth through BDD policies. First published online 15 April 2025